2020
DOI: 10.1186/s12864-020-6448-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of gene expression of Verticillium dahliae upon treatment of the cotton root exudates

Abstract: Background: Cotton Verticillium wilt is one of the most devastating diseases for cotton production in the world. Although this diseases have been widely studied at the molecular level from pathogens, the molecular basis of V. dahliae interacted with cotton has not been well examined. Results: In this study, RNA-seq analysis was carried out on V. dahliae samples cultured by different root exudates from three cotton cultivars (a susceptible upland cotton cultivar, a tolerant upland cotton cultivar and a resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…This hints at a role in aggregate invasion, although the equivalent experiment performed with an S. cerevisiae ecm14Δ mutant did not result in a phenotype [44], suggesting either a false positive in the rst screen or the use of inappropriate conditions for this assay with S. cerevisiae. A transcriptomics study of the plant pathogen V. dahliae showed that the expression of Ecm14, along with a variety of cell wall degrading hydrolases, was upregulated in response to exudates from V. dahliae-susceptible cotton roots [45]. This again points to a possible role for Ecm14 in invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This hints at a role in aggregate invasion, although the equivalent experiment performed with an S. cerevisiae ecm14Δ mutant did not result in a phenotype [44], suggesting either a false positive in the rst screen or the use of inappropriate conditions for this assay with S. cerevisiae. A transcriptomics study of the plant pathogen V. dahliae showed that the expression of Ecm14, along with a variety of cell wall degrading hydrolases, was upregulated in response to exudates from V. dahliae-susceptible cotton roots [45]. This again points to a possible role for Ecm14 in invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This hints at a role in aggregate invasion, although the equivalent experiment performed in S. cerevisiae of the ÎŁ1278b background, which can undergo aggregate invasive growth, did not result in a phenotype [44], suggesting either a false positive in the rst screen or the use of inappropriate conditions for this assay with S. cerevisiae. A transcriptomics study of the plant pathogen Verticillium dahliae showed that the expression of Ecm14, along with a variety of cell wall degrading hydrolases, was upregulated in response to exudates from V. dahliaesusceptible cotton roots [45]. This again points to a possible role for Ecm14 in invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This hints at a role in aggregate invasion, although the equivalent experiment performed in S. cerevisiae of the ÎŁ1278b background, which can undergo aggregate invasive growth, did not result in a phenotype [ 44 ], suggesting either a false positive in the first screen or the use of inappropriate conditions for this assay with S. cerevisiae . A transcriptomics study of the plant pathogen Verticillium dahliae showed that the expression of Ecm14, along with a variety of cell wall degrading hydrolases, was upregulated in response to exudates from V. dahliae -susceptible cotton roots [ 45 ]. This again points to a possible role for Ecm14 in invasion.…”
Section: Discussionmentioning
confidence: 99%